Can changes in angiogenic biomarkers between the first and second trimesters of pregnancy predict development of pre‐eclampsia in a low‐risk nulliparous patient population?. Issue 10 (18th January 2013) - Myatt, L; Clifton, RG; Roberts, JM; Spong, CY; Wapner, RJ; Thorp, JM; Mercer, BM; Peaceman, AM; Ramin, SM; Carpenter, MW; Sciscione, A; Tolosa, JE; et al.
<x xml:space="preserve">Abstract</x> Objective To determine if change in maternal angiogenic biomarkers between the first and second trimesters predicts pre‐eclampsia in low‐risk nulliparous women. Design A nested case–control study of change in maternal plasma soluble Flt‐1 (sFlt‐1), soluble endoglin (sEng) and placenta growth factor (PlGF). We studied 158 pregnancies complicated by pre‐eclampsia and 468 normotensive nonproteinuric controls. Setting A multicentre study in 16 academic medical centres in the USA. Population Low‐risk nulliparous women. Methods Luminex assays for PlGF, sFlt‐1 and sEng performed on maternal EDTA plasma collected at 9–12, 15–18 and 23–26 weeks of gestation. Rate of change of analyte between first and either early or late second trimester was calculated with and without adjustment for baseline clinical characteristics. Main outcome measures Change in PlGF, sFlt‐1 and sEng. Results Rates of change of PlGF, sEng and sFlt‐1 between first and either early or late second trimesters were significantly different in women who developed pre‐eclampsia, severe pre‐eclampsia or early‐onset pre‐eclampsia compared with women who remained normotensive. Inclusion of clinical characteristics (race, body mass index and blood pressure at entry) increased sensitivity for detecting severe and particularly early‐onset pre‐eclampsia but not pre‐eclampsia overall. Receiver operating characteristics curves for change from first to early second trimester in sEng, PlGF and sFlt‐1 with clinical characteristics had areas under the curve of 0.88, 0.84 and 0.86, respectively, and for early‐onset pre‐eclampsia with sensitivities of 88% (95% CI 64–99), 77% (95% CI 50–93) and 77% (95% CI 50–93) for 80% specificity, respectively. Similar results were seen in the change from first to late second trimester. Conclusion Change in angiogenic biomarkers between first and early second trimester combined with clinical characteristics has strong utility for predicting early‐onset pre‐eclampsia.